2017
DOI: 10.1590/s1806-92902017000300004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of photoperiod length and light intensity on some welfare criteria, carcass, and meat quality characteristics in broilers

Abstract: -The objective of this study was to investigate the effects of photoperiod length and light intensity on leg and eye health, tonic immobility, some blood parameters, carcass, and meat quality characteristics in broilers. A total of 272 one-day-old male broiler chicks (Ross 308) were randomly assigned to four treatment groups based on the photoperiod length (23L:1D or increasing duration of light) and light intensity (20 lux vs. dim light) with four replicates. In this study, photoperiod lenght had no effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
30
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 35 publications
8
30
1
1
Order By: Relevance
“…In addition, aside from a trend of higher freezing/thawing loss in 16L:8D (p = 0.098), there was no other impact of photoperiod on WHC. Similarly, other studies have found no impact of photoperiod on WHC [17,36]. No differences in shear force values were also observed across treatments, and, to our knowledge, studies measuring instrumental tenderness of broiler fillet muscles associated with photoperiod effects are unavailable in the current literature.…”
Section: Discussionsupporting
confidence: 46%
“…In addition, aside from a trend of higher freezing/thawing loss in 16L:8D (p = 0.098), there was no other impact of photoperiod on WHC. Similarly, other studies have found no impact of photoperiod on WHC [17,36]. No differences in shear force values were also observed across treatments, and, to our knowledge, studies measuring instrumental tenderness of broiler fillet muscles associated with photoperiod effects are unavailable in the current literature.…”
Section: Discussionsupporting
confidence: 46%
“…It is noticed from Table 2 that there was no significant effect for all lighting systems in the sixth and seventh weeks of age in the dressing yield without and with edible organs. These results agreed with each of the researchers (Fidan et al, 2017a andOlanrewaju et al, 2018) who noted no significant differences in the dressing yield when using different lighting systems. The same table also indicates that there were no significant differences in the relative weights of carcass parts at the sixth week of age, and it was in agreement with the results of Adabi et al (2007) and Coban et al (2014).…”
Section: Discussionsupporting
confidence: 90%
“…Light intensity plays an important role in broiler's health (Blatchford et al, 2012). Studies showed that low light intensity has negative effects on broiler's carcass traits, early uniformity and meat tenderness, and is in relation to incidence of leg disease, eye defects, dystrophy, skeletal disorders, as well as foot pad health (Blatchford et al, 2009;Deep et al, 2012;Senaratna et al, 2016;Fidan et al, 2017;Rault et al, 2017). High light intensity can improve activity (Blatchford et al, 2012;Rault et al, 2017) and benefit bone health (Blatchford et al, 2009), increase growth and breast muscle percentage (Deep et al, 2013), and give comfort behaviors for broilers (Alvino et al, 2009).…”
Section: Introductionmentioning
confidence: 99%